Public Saving, a Social Vice: Is Keynes Right? Sub-Saharan Africa Economic Growth in Perspective - Adediyan, Aderopo Raphael (Asian Development Policy Review, 2019)
Several of Classical growth models pointed out saving as a condition that guarantees economic growth under the presupposition that adequate saving secures adequate capital formation. However, the new wave of ideas that rocks the macroeconomic landscape in the 1930s gave a new insight into the relationship with more focus on the consumption than saving. Most countries in Sub-Saharan Africa had consistently pursued consumption-stimulating policy in lieu of saving; albeit, owing to insufficient capital to produce what they consume, rising public debt, inflation, unemployment and others are the end results. Thus, this paper examined the role of saving on growth in sub-Saharan Africa using a panel cointegration, DOLS and SVECM methods. The study, in addition to the long run relationship established, suggested that while in the long run saving has a positive impact on growth, in the short run, Keynes “effect” seems to hold – saving had a prolonged negative shock on growth, with the implication that sub-Saharan Africa must face a trade-off between having an accumulated saving to increase economic growth in the long run and getting rapid economic growth in the short run.